The Effect of Water Safety Education Programme on Knowledge and Attitudes Towards Water Safety and Survival Swimming Skills among First-year University Students in Sri Lanka: A Mixed-Method Study - Jeewanthika Sanya Kumari Ekanayaka, Ekanayaka Mudiyanselage (Universiti Malaysia Sarawak, 2022)
Drowning is a major public health problem in Sri Lanka due to its local geographical features and frequent flooding. Young adults aged 15-24 years and those between 25-44 years constitute the significant number of drowning deaths in Sri Lanka. Improvement of water safety knowledge, attitudes, and survival swimming skills is vital to reduce drowning risks among the young adult population. Prevention of drowning is crucial, rather than management of drowning-related complications and rehabilitation. This study aimed to assess the influence of a water safety education programme, “Swim for Safety,” on water safety knowledge, attitudes, and survival swimming skills among first-year undergraduates in a public university in Sri Lanka. The study employed a mixed-method study design using a parallel-group, two-arm randomized controlled trial and qualitative approach among 156 participants. The intervention group (n=78) received a face-to-face, 12-lesson ‘Swim for Safety’ programme, and the control group (n=78) received a brochure and weekly mobile phone messages for six consecutive weeks. Participants’ water safety knowledge, attitudes, and survival swimming skills were evaluated at baseline, immediate post- intervention, and follow-up at three months after the intervention, using a self-administered questionnaire and a skills assessment protocol checklist. The experience of participants from the intervention group was explored through focus group interviews. Quantitative data were analyzed with descriptive analysis, Wilcoxon signed-rank test, and Mann-Whitney U test using SPSS [Version 22], and qualitative data were analyzed using thematic analysis. A total of 116 participants completed the study, including 60 participants for the intervention and 56 for the control group. Among them, 60% (n=36) in the intervention and 41.1% (n=23) in control were swimmers. The intervention group showed a statistically significant improvement (P<0.05) in median scores from their baseline of water safety knowledge, water safety attitudes, and survival swimming skills scores at the immediate post-intervention measurement time point, as compared to the control group. However, there was no significant change in the median knowledge, attitudes, and skills scores at the three-month follow-up measurement time point in both groups as compared to the immediate post-intervention measurements. Three main themes which emerged from the qualitative analysis were facilitators for participation, challenges for participation and sense of satisfaction with programme. In conclusion, the “Swim for Safety” program significantly improved the water safety knowledge, attitudes, and survival swimming skills among first-year university students in Sri Lanka. The “Swim for Safety” program could be further recommended to university students in Sri Lanka. Public health nurses can be involved in extending the “Swim for Safety” programme to university students in partnership with other public health care professionals, water safety experts, and other relevant stakeholders.